Ten‐Year Post‐traumatic Osteoarthritis Incidence Is Low After Pediatric Isolated Meniscal Surgery but Lower After Meniscal Repair Than Meniscectomy - Annika N. Hiredesai; Alejandro M. Holle; Jay R. Patel; Katelyn T. Koschmeder; Sailesh V. Tummala; Jeffrey M. Vaughn; Karan A. Patel (Arthroscopy, Sports Medicine, and Rehabilitation, 2026)
Purpose To examine the 5‐ and 10‐year incidence of post‐traumatic osteoarthritis (PTOA) after isolated, primary meniscal surgery differentiating between meniscal repair and meniscectomy, in pediatric patients. Methods Pediatric patients (≤16 years) undergoing primary meniscectomy or meniscal repair (2010‐2023) with ≥5‐year follow‐up were identified in the PearlDiver database. Exclusion criteria included prior or concomitant knee injuries, surgeries, or syndromes. Delayed surgery was defined as ≥90 days after diagnosis. PTOA diagnosis was defined by billing codes. Motion restoration procedures (MRPs) before PTOA diagnosis were recorded. Multivariable logistic and Cox regression were used to assess risk factors for PTOA at 5 and 10 years. Results A total of 7555 meniscectomy (mean age 14.7, 50% women) and 2797 meniscal repair (mean age 14.4 years, 46% women) patients met inclusion criteria. At 5 years, PTOA occurred in 2.2% of meniscectomy and 1.4% of repair patients. At 10 years, rates were 2.3% and 1.5%, respectively. Average time to PTOA was 737 days (meniscectomy) and 862 days (repair). When disaggregated by sex, there was no significant difference in sex makeup of those who did and did not develop PTOA ( P = .430). In the meniscectomy group, risk factors for 10‐year PTOA included MRP (hazard ratio [HR] 6.28, P < .001), age ≥12 at surgery (HR 4.84, P = .027), and obesity (HR 1.84, P < .001). In the repair group, MRPs (HR 5.23, P = .023) and depression (HR 2.02, P = .027) were significant. These same risk factors were identified for 5‐year PTOA. Conclusions The 10‐year incidence of PTOA was 2.2% after meniscectomy and 1.5% after meniscal repair in pediatric patients. MRPs were a consistent risk factor. Age ≥12 and obesity were associated with PTOA after meniscectomy. Depression was associated with PTOA after repair. Level of Evidence Level III, retrospective cohort study.